Pengaruh Pengetahuan Perpajakan, Sosialisasi Perpajakan, dan Penerapan Layanan SAMSAT Keliling pada Kepatuhan Wajib Pajak - Ardiyanti, Ni Putu Mita; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 30 No 8 (2020)DO - 10.24843/EJA.2020.v30.i08.p02, 2020)
The research aims to examine the factors that can affect taxpayer compliance by referring to the Attribution theory. These factors are taxation knowledge, taxation socialization and mobile SAMSAT services. The SAMSAT Office in Bangli Regency was chosen as a place of research. The number of respondents taken was 100 taxpayers using the accidental sampling method. Data collection using a questionnaire, then analyzed by multiple linear regression test. The analysis shows that tax knowledge, tax socialization, and mobile SAMSAT services have a positive effect on taxpayer compliance. Regional Revenue Agency of Bali Province should provide periodic outreach, as well as increase the location and schedule of mobile SAMSAT services to increase taxpayer compliance. Keywords: Taxation Knowledge; Tax Socialization; SAMSAT Mobile; Taxpayer Compliance.